Proprotein convertase subtilisin/kexin 9 (PCSK9) in patients with diffuse systemic sclerosis: A marker of disease activity and severe disease manifestations with potential therapeutic implementations - Joy Artin,; Yumn A. Elsabagh,; Laila Rashed,; Mohamed A. Hussein, (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate proprotein convertase subtilisin/kexin 9 (PCSK9) in patients with diffuse systemic sclerosis (d-SSc) and its relation to disease activity, severity and subclinical atherosclerosis in such group of patients. Patients and methods: Between December 2019 and July 2021, a total of 41 patients with d-SSc (17 males, 24 females; mean age: 36.1±1.9 years; range, 19 to 58 years) and 41- age and sex-matched healthy controls (17 males, 24 females; mean age: 40.1±1.7 years; range, 20 to 60 years) were included. Disease activity and skin thickness of the patients were evaluated using the European Scleroderma Study Group (EScSG) score and modified Rodnan skin score (mRSS), respectively. Serum PCSK9 and carotid intima-media thickness (CIMT) were measured using enzyme-linked immunosorbent assay (ELISA) and Duplex ultrasound, respectively. Results: Serum PCSK9 was higher in patients compared to controls (p=0.003), particularly in those with digital ulcer (DU) and interstitial lung disease (ILD) (p<0.001). The PCSK9 positively correlated with the mean pulmonary artery pressure, EScSG, mRSS, C-reactive protein (p<0.001), erythrocyte sedimentation rate (p<0.05), lipid profile, and mean CIMT (p<0.01). In the multivariate analysis, EScSG, mRSS, lipid profile, and waist circumference were significantly correlated with PCSK9. Serum PCSK9 levels of (182.6 ng/mL) had 77.7% sensitivity and 81.2% specificity for diagnosing DU versus (172.8 ng/mL) 90.1% and 73.5% for ILD (p<0.001). Conclusion: Serum PCSK9 is upregulated in d-SSc with higher levels in severe disease manifestations such as DU and ILD. It is correlated well with disease activity, more severe disease manifestations, and CIMT. The PCSK9 inhibitors may be a target of therapy in diseases with premature atherosclerosis such as d-SSc regardless of its anti-cholesterol effect, at least in more severe manifestations.